PERANCANGAN STRUKTUR KEMASAN MAKANAN AKAR KELAPA: Design of Packaging Structure for Coconut Root Food - Rachmadita Dwi Pramesti; Susilawati; Gabriela Oktavia Siregar; Regi Jusnia Ramli (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2024)
Packaging is one of the keys for MSMEs to further increase the selling value of the product. Packaging has an important role because it relates to the product it packs and is the selling point of the product and displays the product image. This selling value increases when the product gets added value from an attractive packaging design. One of the attractions of a packaging is its practical or functional appeal. The packaging design variable consists of 3 dimensions, namely: graphic design, structure design, and product information. The design structure is related to the physical features of the packaging, and consists of 3 sub-dimensions, namely shape, size, and material. Folding cardboard is one of the packaging materials included in the packaging structure. Paper and cardboard packaging are the most favored by the global market segment which accounts for up to 31% because they have many functions such as means for protection and food products. This study uses a descriptive qualitative approach with the Design Thinking method which includes Define, Research, Ideate, Prototype, Select, Implement, and Learn to get the results of the packaging structure design design including the shape and material or packaging material to add value to the product with its unique packaging form. The result of this design is a packaging structure with a prism shape and a lock using a tuck end at the top and a bottom lock for the bottom of the package. The structure is able to provide efficient use of packaging from the ease of opening and closing the packaging and packaging ergonomics.